The value of music appreciation for students - Na, Zhang; Fernando, Yudi (PT. Berbagi Teknologi Semesta, 2024)
The significance of music and the appreciation that music brought to student lives was the driven force behind the study. The study has found that music plays an important role in the development of a student from the early stage which is why it has been recommended that student should be introduced to music to have a link with their heritage and history.Teaching music and songs are critical in cultural transfer from one generation to the next generation which without it many values inherited from the ancestors may go into extinction. Thus, one of the ways this can be achieved is the teaching of songs and music especially of the old generation so that the new generation can catchup with their history and culture. The study further recommends that sustaining music and songs in schools from the early stage of kindergarten to university level can further enhance the cultural integration and it will make the students not to far away from their heritage and history.